Introduction - Czamańska, Ilona; Diaconescu, Marius (Balcanica Posnaniensia. Acta et studia, 2015)
The importance of the Vlachs in European culture remained unnoticed for many years. They were considered a small group of Romanised shepherds, and not a very highly developed culture, with not a great importance for the development of civilization. The specificity of the culture of the Vlachs, primarily due to its folkloristic character, wasn’t understood or appreciated. It was not realized that the management of the herds in the mountains required big skills and knowledge, and that Vlachs played an important role in the dissemination of the shepherd culture. Only recently the role of the Vlach law in shaping the social and military system of the late medieval and the early modern societies is being recognized. The role of the Vlach agent, as an important element in the formation of nationality, particularly in the Balkans, is also beginning to be perceived. Only recently it started being noticed that the Vlachs, are not just this group which has preserved its Romance language, but also numerous groups which assimilated long ago, preserving a greater or lesser extent, their traditional culture. The characteristic treatment of the Vlach population, except this part which evolved into the Romanian nation, consisted in its ease of coexistence with other ethnic groups and cultures. The Vlachs were mostly a non-state nation, and it contributed largely to the fact that their history and cultural characteristics are, after all, fairly poorly understood. Therefore, there is a great need for a new extensive research undertaken in international cooperation and for the publication of the results of these studies. For this purpose, the international research project Vlachs in European and Polish cultural area. Migration — settlement — cultural heritage has been launched. However, before the project was qualified to be financed, two institutes: the Institute of History of the Adam Mickiewicz University in Poznan and The Faculty of History at the University of Bucharest have taken a joint initiative of annual meetings of researchers on the Vlachs and the publishing series that would became space both for the publication of materials, as well as a discussion forum. The result of this initiative was a conference organized jointly in October last year in Bucharest. The next step is the joint publication of the Ius Valachicum, whose first volume we put into the hands of readers.